The construction of houses series III [videorecording] : finishes (Bristol : The Video Project, 2010)
This film covers the principles and application of external and internal renders. The last part of the films looks at internal partitions. Using a mixture of site footage, photos and graphics, the film covers the following areas: - Historical overview - External renders - Lime, gypsum and cement based internal plasters - Dry lining - Ceilings - Internal partitions - old and new